Efektivitas Permainan Ular Tangga terhadap Hasil Belajar Perkalian pada Siswa Kelas III di SDN 3 Pamalayan - Ary Ananda Gustianov (Indonesian Journal of Integrated Science and Learning, 2025)
This study aimed to improve students’ multiplication learning outcomes through the implementation of the snakes and ladders learning model at SDN 3 Pamalayan. The study employed Classroom Action Research conducted in two cycles. The subjects of the study were 16 third-grade students of SDN 3 Pamalayan. The data collection techniques included written tests, observation, interviews, and documentation. The data were analyzed using qualitative analysis to describe the learning process and students’ participation, and quantitative analysis to determine the improvement in students’ average learning outcomes in each cycle. The results showed that the use of snakes and ladders as a learning medium was able to improve students’ learning outcomes, active participation in group discussions, and create a more interactive and enjoyable learning atmosphere. A more significant improvement was found in the second cycle after instructional improvements had been made. The implication of this study is that snakes and ladders can be used as an alternative mathematics learning strategy that is innovative, interactive, and appropriate to the characteristics of elementary school students, particularly in improving their understanding of multiplication and their learning outcomes.